2015
DOI: 10.1159/000382070
|View full text |Cite
|
Sign up to set email alerts
|

Complete Endoscopic Submucosal Dissection of a Giant Rectal Villous Adenocarcinoma with Electrolyte Depletion Syndrome

Abstract: An 81-year-old female consulted a local physician due to diarrhea. Since general fatigue and body weight loss were observed, she was admitted for detailed examination and treatment. Colonoscopy revealed a circumferential giant tumor with a maximum diameter of 10 cm in the rectum, and biopsy findings indicated villous adenoma. The tumor secreted a large amount of mucus, and a diagnosis of electrolyte depletion syndrome causing electrolyte disorders was made. We performed endoscopic submucosal dissection (ESD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…2 Definitive treatment remains resection of the underlying lesion either surgically or endoscopically. 3 Our patient had resolution of diarrhea after endoscopic resection of the polyps with restoration of potassium to normal value without further need for supplementation. He has been counselled regarding the need for surveillance colonoscopies as per recommendations for high-grade dysplasia in a tubulovillous adenoma.…”
mentioning
confidence: 59%
“…2 Definitive treatment remains resection of the underlying lesion either surgically or endoscopically. 3 Our patient had resolution of diarrhea after endoscopic resection of the polyps with restoration of potassium to normal value without further need for supplementation. He has been counselled regarding the need for surveillance colonoscopies as per recommendations for high-grade dysplasia in a tubulovillous adenoma.…”
mentioning
confidence: 59%
“…A meta-analysis of 18 studies showed that the prevalence of villous adenoma as the pathological type among all colonic polyps was 5.7% 9. Of these villous adenomas, a range from 0.76 to 2.4% of them will become secretory in nature,8 making the prevalence of secretory villous adenoma 0.01% of all colonic polyps.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the mainstay surgical option was complete resection of the involved area of the colon or rectum. Today, numerous surgical options are being researched and considered, including endoscopic submucosal dissection 8. Even though surgical management is the definitive treatment, it is necessary to correct the severe electrolyte abnormalities that these patients exhibit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definitive treatment is partial colectomy followed by fluid and electrolyte replacement. An endoscopic approach is a limited option because of its circumference, malignancy, and location [24]. Especially in the case of tumors located in the lower rectum, we cannot avoid choosing abdominal–peritoneal resection, which reduces the patients’ quality of life drastically.…”
Section: Introductionmentioning
confidence: 99%